Adsorption of dyes using activated carbons - Cai, Hui Yang (2010)
Activated carbons are commonly used in adsorption of dyes and chemicals. In this work, the adsorption capabilities of large and fine granular activated carbons were investigated using equilibrium batch and fixed bed column.